2018
DOI: 10.1134/s1990341318010042
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolutionary State of High-Latitude Variable V534 Lyr

Abstract: Based on the high resolution spectral monitoring conducted at the 6-m BTA telescope, we study the optical spectrum of the high-latitude variable V534 Lyr. Heliocentric radial velocities V r corresponding to the positions of all metal absorption components, as well as the Na I D and Hα lines were measured during all the observational dates. The analysis of the velocity field examining the lines of various nature revealed a low-amplitude variability of V r based on the lines with a high excitation potential, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…In the course of subse-quent evolution, it may approach the instability band, and then the AGB stage. The authors [101] eventually concluded on the discrepancy of the V534 Lyr belonging to the post-AGB stage.…”
Section: A Star At the Stage Of Evolution Before Agbmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of subse-quent evolution, it may approach the instability band, and then the AGB stage. The authors [101] eventually concluded on the discrepancy of the V534 Lyr belonging to the post-AGB stage.…”
Section: A Star At the Stage Of Evolution Before Agbmentioning
confidence: 99%
“…Based on multiple observations at the 6-m telescope with the NES echelle spectrograph, we thoroughly studied the features of the optical spectrum of V534 Lyr and the temporal behavior of the heliocentric radial velocity corresponding to the position of all the metal absorption components as well as the Na I D-lines and the Hα line [101]. The analysis of the velocity field of spectral features of various nature revealed a low-amplitude variability of V r from the lines with a high excitation po- tential, which form in deep layers of the stellar atmosphere, and allowed to estimate the systemic velocity V lsr ≈ −105 km s −1 .…”
Section: A Star At the Stage Of Evolution Before Agbmentioning
confidence: 99%
“…It is a small amplitude light and radial velocity variable. Recently, Klochkova et al (2018) made detailed analysis of the high resolution spectra of this star and derived its chemical composition. They find T eff = 10,000K, log g = 2.5.…”
Section: • Ls 5107 (Iras 18365-1353)mentioning
confidence: 99%
“…They conclude that it is a population-II pulsating star near the horizontal branch. Klochkova et al (2018) derived a distance of 6 kpc, whereas Bonsack, & Greenstein (1956) estimated a distance of 5.7 kpc. The Gaia DR 2 data (Tables 1 and 2), however, clearly shows that their distance estimate is wrong.…”
Section: • Ls 5107 (Iras 18365-1353)mentioning
confidence: 99%
See 1 more Smart Citation